Identity Commodification as a Strategy for Acehnese Culinary Business Development: A Comparative Analysis of Indonesia and Egypt - Agustinar, Agustinar; Mufida, Laila; Sumarni, Mutia; Ishak, Munawwar (State of Islamic Institute Langsa, 2025)
Ideally, identity commodification can be an effective strategy in the development of the culinary business by utilizing local cultural and religious values as an attraction for consumers. However, in reality, significant challenges arise in the implementation of this strategy, especially related to cultural diversity and the dynamics of the global market. This study aims to analyze the application of identity commodification in the development of Acehnese culinary businesses, and compare it with the approach applied in Egypt. This article is a field study using a qualitative approach. The methodology employed includes descriptive analysis and comparative study. The research findings show that Aceh has successfully utilized its local identity, which is deeply rooted in Islamic culture, as an appealing culinary business strategy, with a strong halal guarantee even without official halal certification. A comparison with Egypt shows that, although both leverage cultural and religious identity, Aceh emphasizes the diversity of local cultures combined with religious values, while Egypt focuses more on preserving the authentic Arab-Islamic culinary traditions and history.